2014
DOI: 10.1111/joss.12124
|View full text |Cite
|
Sign up to set email alerts
|

Learning Odors: The Impact of Visual and Olfactory Mental Imagery Training on Odor Perception

Abstract: Mental imagery has been used successfully in sensorimotor training, but rarely to improve sensory skills. Novices, undergraduate enology students (intermediates) and wine experts were asked to repeatedly imagine the visual images or smells of odorant sources presented in picture form. Olfactory abilities, odor sensitivity and identification performance were compared before and after mental training to check the differential effects of the two types of sensory training. We demonstrated that, like repeated objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…When asked to just sniff either diacetyl or linalool every day for 1 month, experts were better able to detect the trained odor (Tempere, Cuzange, Bougeant, Revel, & Sicard, 2012). In fact, just imagining odors appears sufficient to improve detection for the imagined smell (Tempere, Hamtat, Bougeant, de Revel, & Sicard, 2014).…”
Section: More Than Mere Exposure-the Making Of An Odor Expertmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked to just sniff either diacetyl or linalool every day for 1 month, experts were better able to detect the trained odor (Tempere, Cuzange, Bougeant, Revel, & Sicard, 2012). In fact, just imagining odors appears sufficient to improve detection for the imagined smell (Tempere, Hamtat, Bougeant, de Revel, & Sicard, 2014).…”
Section: More Than Mere Exposure-the Making Of An Odor Expertmentioning
confidence: 99%
“…At present, however, it is unclear how such training compares with the mere exposure paradigm, and to what extent the improvements in discrimination generalize to new odors. To our knowledge, no study has utilized a more active training strategy to improve odor sensitivity, except Tempere, Hamtat, et al (2014) who found mental imagery training for specific odors improved odor detection. It is possible that such active training could benefit odor discrimination performance more (as compared with mere exposure training) because discrimination is a higher level process than odor detection.…”
Section: More Than Mere Exposure-the Making Of An Odor Expertmentioning
confidence: 99%
“…The expert's workplace has been identified as a key factor contributing to the continuous development of expertise (Tynjälä, ), and thus, the development of a workplace as a learning environment has been emphasized. Previous literature on sensory training has emphasized an individual's work in light of assessor training methods, for example, mental imagery (Tempere, Hamtat, Bougeant, Revel, & Sicard, ) and computerized panel training (Kuesten, McLellan, & Altman, ). Collaborative interaction as a training method has been mentioned in a study by Marchisano, Vallis, and Macfie () in which the results showed that there was no evidence that the feedback had positive effects on performance in triangle tests or scaling.…”
Section: Discussionmentioning
confidence: 99%
“…Clear agreement between experts concerning typicality scores (Ballester et al 2008) and existence of shared cognitive constructs of typicality (Urdapilleta et al 2011) have been demonstrated. Descriptions stored in longterm memory can be used to generate images of objects and scenes (Tempere et al 2014). Flavor may be processed by tasters as a psychological construct, the data being more consistent with a perceptual/cognitive process rather than a consequence of rating strategies (Prescott 1999).…”
Section: Introductionmentioning
confidence: 99%